2006
DOI: 10.1186/1743-7075-3-5
|View full text |Cite
|
Sign up to set email alerts
|

Further evaluation of plasma sphingomyelin levels as a risk factor for coronary artery disease

Abstract: BackgroundSphingomyelin (SM) is the major phospholipid in cell membranes and in lipoproteins. In human plasma, SM is mainly found in atherogenic lipoproteins; thus, high levels of SM may promote atherogenesis.MethodsWe investigated in a median follow up of 6.0 years the association of SM with the incidence of a combined endpoint (myocardial infarction and cardiovascular death) in stable and unstable patients, and its relation to other marker of atherosclerosis in 1,102 patients with angiographically documented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
63
2
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 36 publications
1
63
2
1
Order By: Relevance
“…We found that higher plasma SM levels and SM/PC ratios are independent risk factors for coronary heart disease (19,20). We believe that LDL retained in atherosclerotic lesions is acted on by an arterial wall sphingomyelinase, which promotes aggregation by converting SM to ceramide (10 -12).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…We found that higher plasma SM levels and SM/PC ratios are independent risk factors for coronary heart disease (19,20). We believe that LDL retained in atherosclerotic lesions is acted on by an arterial wall sphingomyelinase, which promotes aggregation by converting SM to ceramide (10 -12).…”
Section: Discussionmentioning
confidence: 91%
“…It has been shown that plasma SM levels in these mice are 4-fold higher than in WT animals (16), and this may contribute to increased atherosclerosis (17,18). It has also been shown that in humans, higher plasma SM levels and SM/PC ratios are independent risk factors for coronary heart disease (19,20). All these data suggest that plasma SM plays a critical role in the development of atherosclerosis.…”
mentioning
confidence: 93%
“…Likewise, it was reported recently that animals overexpressing PLTP exhibit hepatic very low density lipoprotein (VLDL) overproduction (7) and increased athero-susceptibility (8). Associations of plasma PLTP activity with elevated apoB levels (9) and increased cardiovascular risk (10) have been found in humans as well. These findings have led to an interest in PLTP as a potential therapeutic target.…”
mentioning
confidence: 96%
“…Changes in SM were most closely related to PE, and Cer to lysoPC (Figure S6). A trend in reduced plasma SM levels has been previously reported for patients undergoing statin treatment 38 . These results show a clear difference in the effect of monotherapy vs. combination therapy upon circulating levels of the ratio SM|Cer/(SM|Cer+PC).…”
Section: Discussionmentioning
confidence: 54%
“…Another potential mechanism for pleiotropic effects was observed in an analysis of the relative levels of SM and PC, the SM/(SM+PC) ratio, of which both increases 37, 38 and decreases 39 have been reported to be associated with increased cardiovascular risk. The SM/PC ratio has been suggested as diagnostic marker for increased lipoprotein modifications in hyperlipidemic patients 40 .…”
Section: Discussionmentioning
confidence: 99%